Mouse Polyomavirus: Propagation, Purification, Quantification, and Storage - Horníková, Lenka; Žíla, Vojtěch; Španielová, Hana; Forstová, Jitka (Current protocols in microbiology, 2015)
Mouse polyomavirus (MPyV) is a member of the Polyomaviridae family, which comprises non-enveloped tumorigenic viruses infecting various vertebrates including humans and causing different pathogenic responses in the infected organisms. Despite the variations in host tropism and pathogenicity, the structure of the virions of these viruses is similar. The capsid, with icosahedral symmetry (ø, 45 nm, T = 7d), is composed of a shell of 72 capsomeres of structural proteins, arranged around the nucleocore containing approximately 5-kbp-long circular dsDNA in complex with cellular histones. MPyV has been one of the most studied polyomaviruses and serves as a model virus for studies of the mechanisms of cell transformation and virus trafficking, and for use in nanotechnology. It can be propagated in primary mouse cells (e.g., in whole mouse embryo cells) or in mouse epithelial or fibroblast cell lines. In this unit, propagation, purification, quantification, and storage of MPyV virions are presented.
Keywords: Virus Cultivation; virus quantification; Animals; mouse polyomavirus; Cells, Cultured; kultivace virů; zvířata; Mice; Viral Load; virová nálož; density gradient purification; Preservation, Biological; Polyomavirus; ochrana biologická; kultivované buňky; polyomavirus; myši